FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERNIKAHAN USIA DINI PADA REMAJA DI DESA BIRA KECAMATAN TABUKAN TENGAH KABUPATEN KEPULAUAN SANGIHE - Sandrawati, Jeifen (Journal Of Community & Emergency, 2024)
Early marriage is a marriage that is carried out officially or unofficially before the age of 20. The causes of early marriage in Indonesia are influenced by many factors, including low education, economic needs, and exposure to the mass media. This study aims to determine the factors associated with early marriage in adolescents in Bira Village, Central Tabukan District, Sangihe Archipelago Regency. This study uses a quantitative descriptive approach with a correlation research design, which aims to correlate factors of education level, economic factors and mass media factors with early marriage. Data collection used a questionnaire with a population of 38 adolescents aged 12-25 years who met the inclusion criteria. This research was conducted from December 2022. The data analysis used was the Chi Square test (C²). The results showed that there was a relationship between the factors of the respondent's education level and early marriage in adolescents in Bira Village, Central Tabukan District, Sangihe Islands Regency, with a value of p = 0.000 (p < α = 0.05). There is a relationship between economic factors and early marriage in adolescents in Bira Village, Central Tabukan District, Sangihe Archipelago Regency, Bira Village, Central Tabukan District, Sangihe Islands Regency, obtained p value = 0.000 (p <α = 0.05). There is a relationship between the Mass Media factor and early marriage in adolescents in Desa Bira Sub-District, Central Tabukan District, Sangihe Archipelago Regency. The statistical test results with Chi Square obtained p = 0.000 (p <α = 0.05). This research can be used as a contribution of information to the public about what factors are related to early marriage and the impact on health so that people can know the dangers of early marriage.